Azidation of Partially Protected Carbohydrate Derivatives: Efficient Suppression of Acyl Migration - Stepanova, Elena V.; Zinin, Alexander I.; Abronina, Polina I.; Chizhov, Alexander O.; Kononov, Leonid O. (Synlett, 2020)
Although azidation by nucleophilic substitution is widely used in organic chemistry, it has a limitation for partially protected carbohydrate derivatives under typical reaction conditions used for azidation (heating with NaN3, phase-transfer catalyst (optional), DMF or DMSO) as it can cause substantial migration (70%) of O-acyl protective groups. Several approaches, including the use of a temporary protective group for the unprotected hydroxyl group, to avoid acyl migration have been compared. Addition of excess of ethyl trifluroacetate effectively suppressed benzoyl migration but inhibited substitution of the chlorine atom with the azido group. The most robust procedure involved addition of excess n-butyl formate to the reaction mixture. When this protocol was followed, migration of benzoyl groups in lactose derivatives with free hydroxy group at C-3′ or C-4′ was reduced to 4%, with the yield of the target, partially protected derivatives with an azido group in the aglycone approaching 92%.
Keywords: azide; carbohydrate; protecting group; regioselectivity